Development of Management Information System Based on Android Application at Al-Anwari High School - Jaya, Hendra; Putra, Yuniarti Hidayah Suyoso (Journal of Education Method and Learning Strategy, 2024)
This study aims to portray the development of information systems at SMA al-Anwari Bangkalan based on android applications. The research method uses a descriptive qualitative approach. The results show that the Development of Management Information System (SIM) Based on Android Application at Al-Anwari High School reflects the progressive transformation in the world of education towards the digital era. This article investigates the needs, benefits, and main functions of this application, as well as discussing system integration, security and privacy aspects, and the importance of training and mentoring. The implementation of this app at Al-Anwari High School brings significant benefits to teachers, students, parents and administrative staff by providing easy, quick and integrated access to academic and school management information. The main functions of the application involve schedule management, attendance recording, academic information, parent-teacher communication, and extracurricular management.